Seafloor geomagnetic sounding near the 85°E ridge in the bay of Bengal - Joseph, E. John; Iyengar, R.V.; D'Cruz, L.A.; Singh, B.P. (My University, 1995)
Seafloor geomagnetic field variations in three components were recorded in the Bay of Bengal near the 85°E ridge, to investigate whether the negative gravity anomaly over the ridge is due to thick sedimentary deposit or due to a thick crust. Comparison of the X-, Y-and Z-variations in the vicinity of the 85°E ridge and near the continental margin suggests that a resistive thick crust underlies the 85°E ridge. The validity of conclusions arrived at from a simple inspection of magnetograms is supported by numerical calculations using a thin sheet approximation.
Keywords: Geomagnetic sounding; Bay of Bengal; Sedimentary; Geomagnetic field